Trypanosoma brucei gambiense group 1 is distinguished by a unique amino acid substitution in the HpHb receptor implicated in human serum resistance. - Rebecca E Symula; Jon S Beadell; Mark Sistrom; Kehinde Agbebakun; Oliver Balmer; Wendy Gibson; Serap Aksoy; Adalgisa Caccone (PLoS Neglected Tropical Diseases, 2012)
Trypanosoma brucei rhodesiense (Tbr) and T. b. gambiense (Tbg), causative agents of Human African Trypanosomiasis (sleeping sickness) in Africa, have evolved alternative mechanisms of resisting the activity of trypanosome lytic factors (TLFs), components of innate immunity in human serum that protect against infection by other African trypanosomes. In Tbr, lytic activity is suppressed by the Tbr-specific serum-resistance associated (SRA) protein. The mechanism in Tbg is less well understood but has been hypothesized to involve altered activity and expression of haptoglobin haemoglobin receptor (HpHbR). HpHbR has been shown to facilitate internalization of TLF-1 in T.b. brucei (Tbb), a member of the T. brucei species complex that is susceptible to human serum. By evaluating the genetic variability of HpHbR in a comprehensive geographical and taxonomic context, we show that a single substitution that replaces leucine with serine at position 210 is conserved in the most widespread form of Tbg (Tbg group 1) and not found in related taxa, which are either human serum susceptible (Tbb) or known to resist lysis via an alternative mechanism (Tbr and Tbg group 2). We hypothesize that this single substitution contributes to reduced uptake of TLF and thus may play a key role in conferring serum resistance to Tbg group 1. In contrast, similarity in HpHbR sequence among isolates of Tbg group 2 and Tbb/Tbr provides further evidence that human serum resistance in Tbg group 2 is likely independent of HpHbR function.